Sediment echosounder raw data (Atlas Parasound P70 echosounder entire dataset) of RV MARIA S. MERIAN during cruise MSM125 - Miriam Römer; Yann Marcon; Christian Borowski (PANGAEA, 2025)
Sediment echosounder data using Atlas Parasound P70 echosounder was recorded during MARIA S. MERIAN cruise MSM125. The expedition took place during 30.01.2024 - 06.02.2024 from Algeciras (Spain) to Funchal (Portugal) in the Northern Atlantic. Data were recorded in the Moroccan and Portuguese EEZs and outside. MSM125 was a short cruise of only four working days to test deep-sea research devices developed at MARUM at the University of Bremen and the Max Planck Institute for Marine Microbiology, Bremen (MPIMM), as part of the Cluster of Excellence The Ocean Floor - Earth extquotesingles Uncharted Interface in in-situ operation so that they can be used in future research expeditions. During the cruise, the hull-mounted parametric sub-bottom profiler ATLAS PARASOUND P70 was used to conduct information about the sediment sub-surface and water column. Its function is based on the parametric effect of the non-linear relation of pressure and density during sonar propagation. The system utilizes two high-intensity waves with frequencies of 18-20 kHz (primary high frequency; PHF) and 22-24 kHz to create a secondary high (about 40-42 kHz) and secondary low frequency (SLF) of about 4 kHz. The SLF can record sub-bottom structures, whereas the PHF can image the water column and potential gas bubbles, plankton, fish or nepheloid layers within. The transducer array has an opening angle of 4° by 5°, which corresponds to a footprint size of about 7% of the water depth. Data acquisition was performed using measured real-time values of surface sound velocity and a static sound velocity profile of 1500 m/s. Using the software ATLAS PARASTORE, data was displayed and stored as raw *.asd files and additional *.ps3 and auxiliary files for certain depth windows. The sub-bottom profiler was operating almost continuously with a desired frequency of 4 kHz for SLF and a desired frequency of 18 kHz for PHF.